Physical activity as a non pharmacological intervention in Alzheimer’s disease: a narrative review - Zaborowska, Sabina; Pawlak, Paulina; Wojcieszuk, Olaf; Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda; Złotnik, Anna; Krzysztofik, Kinga; Klamka, Antoni (Quality in Sport, 2026)
Background. Alzheimer’s disease (AD) is the leading cause of dementia, and disease‑modifying pharmacological options remain limited. Physical activity (PA) has emerged as a promising modifiable factor to mitigate cognitive decline and disease progression. Aim. To synthesize evidence from clinical and mechanistic studies on the effects of PA in AD, with emphasis on cognition, disease course, and key biological pathways. Material and methods. A targeted narrative search of PubMed and Scopus identified English‑language studies (2002–2025), prioritizing randomized controlled trials, systematic reviews, and meta‑analyses of exercise or PA interventions in individuals with AD, mild cognitive impairment, or preclinical AD; additional observational and mechanistic work was used to contextualize clinical findings. Evidence was synthesized qualitatively, without formal risk‑of‑bias assessment or quantitative meta‑analysis, focusing on cognition, neuropsychiatric symptoms, function, quality of life, and major mechanistic domains. Results. Most studies show that PA improves global cognition (especially executive function) and reduces neuropsychiatric symptoms, while memory effects are more limited. Resistance and multicomponent training yield greater cognitive benefits than aerobic exercise alone, likely via enhanced neurotrophic signaling, reduced Aβ/tau pathology, improved insulin sensitivity, attenuated neuroinflammation, and increased cerebral blood flow. Moderate‑intensity PA (≈150–180 min/week) appears optimal, slowing clinical progression most clearly in preclinical and mild AD, although effects on quality of life remain inconsistent. Conclusions. PA is a promising, safe, and accessible non‑pharmacological intervention, particularly in earlier AD stages, and should be considered a core component of strategies to reduce the burden of AD.